Nostalgia as the cultural phenomenon - A. Y. Morozov, (Ukrainian Cultural Studies, 2018)
The article is devoted to the observation of the cultural phenomenon of nostalgia, its social, psychological, ethical and general philosophical aspects. It is shown that nostalgia is based on value-laden memory that helps us differ pleasant and unpleasant, useful and useless, meaningful and meaningless. This value-laden memory has its ethical dimension that deals with moral tradition, our concepts of good and evil, justice and injustice, sense of life and sense of death. We may say that ethical memory is a part of a larger “cultural memory” that enables every kind of social and individual identity. Due to nostalgia the generation`s continuity is established. In the act of nostalgia a person recalls the past but also rebels against actual state of presence. It is affirmed that our time-arrangement of “bad presence” and “good past” is possible because of ontological time regress. Nostalgizing for the past, a man is trying not only to mythologize the latter, but to resurrect it symbolically. Nostalgia’s faith in revival contains a hope for annihilation of time and triumph of eternity. We may call it an archetypical need, a manifestation of ancient mythological and religious motive of death and resurrection. Longing for past accompanies mankind during all its history and especially rises in the postmodern culture – in forms of metaphysical, political and aesthetical nostalgias. Metaphysical nostalgia is the lust for Logos, (God, meaning, truth, the good and the beauty) in the post-nihilistic absurd world, where god is claimed to be dead, and all supreme values are seemed to be devalued. It is also longing for the sacred reality, the being, that postmodern culture is lacked.  Political nostalgia is the lust for the real power, subconscious desire for its increasing, expanding, absolutization. Aesthetical nostalgia is the sadness for the art as symbolic hierarchical structure with definite cultural and historical code as today we observe fakes and simulations, chaos and “metastases of cultural codes” (J. Baudrillard).
Keywords: nostalgia, cultural memory, value-laden memory, time, eternity, sacred, myth, rationalization, nihilism, lust for Logos